PENGEMBANGAN ASDAHIWA SEBAGAI MEDIA PEMBELAJARAN BERBASIS ARTICULATE STORYLINE MATERI DAUR HIDUP HEWAN DI KELAS IV SEKOLAH DASAR - Amir, Zalsadillah Alifiah; Makmun; Iksam; Sukriadi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The development of information technology drives innovation in learning media capable of enhancing the effectiveness of distance learning processes. Science learning on the topic of animal life cycles in elementary schools still relies on conventional media such as textbooks and basic platforms, resulting in students experiencing difficulties in understanding the material and feelings of boredom during learning. This study aims to develop the interactive learning media ASDAHIWA (Articulate Storyline Animal Life Cycle) and to evaluate its feasibility as a valid, practical, and effective learning medium for fourth-grade elementary school students. The research employs a Research and Development (R&D) approach using the ADDIE model, which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. The research subjects consisted of 30 fourth-grade elementary school students and one classroom teacher. Research instruments utilized validation questionnaires with a Likert scale for media experts, material experts, teachers, and students. Data were analyzed using descriptive percentage formulas. The ASDAHIWA media was successfully developed, with material expert validation at 88.89% (highly feasible), media expert validation at 87.50% (highly feasible), teacher response at 87.50% (very good), and student response at 93.56% (very good). This media integrates interactive multimedia in the form of text, images, audio, video, and animation in an HTML5 format that is accessible cross-platform. The ASDAHIWA learning media has been proven feasible and effective in increasing interactivity in science learning on the topic of animal life cycles. It is recommended that schools integrate this media into the curriculum and conduct teacher training to optimize the use of Articulate Storyline technology in learning.